Epidemiological and virological investigations of equine influenza outbreaks in Ireland (2010–2012). (December 2013) - Gildea, Sarah; Fitzpatrick, David A.; Cullinane, Ann
Abstract : Background: Outbreaks of equine influenza (EI) in endemic populations cause disruption and economic loss. Objectives: To identify (i) factors involved in the spread of EI (ii) virus strains responsible for outbreaks (iii) single radial haemolysis (SRH) antibody levels correlating with protection against current virus strains (iv) evidence of vaccination breakdown. Methods: RT‐PCR, virus isolation and SRH were carried out on nasopharyngeal swabs and blood samples collected from horses, ponies and donkeys on affected premises. Data relating to 629 samples from 135 equidae were analysed. Results and conclusions: Outbreaks were sporadic, self limiting and associated with the movement of horses. Vaccination status and age influenced clinical signs of disease while housing and fomites contributed to virus spread. Subclinical infection as defined as a horse which tested positive by one or more of the following; RT‐PCR, virus isolation and seroconversion in the absence of clinical signs, was identified in 9% of animals. Of the horses with up to date vaccination records 32% developed clinical signs. Vaccine breakdown occurred among horses vaccinated with all four commercially available vaccines. Analysis of HA1 sequence data generated for 26 viruses indicated that they all belonged to clade 2 of the Florida sublineage. Higher SRH antibody levels were required for both clinical and virological protection than reported in studies where vaccine strains were antigenically and genetically similar to those circulating in the field. The results of this study therefore support the OIE recommendations that vaccines be updated to include representatives of both clades of the Florida sublineage.